Living on a fare: Modeling and quantifying the effects of fare budgets on transit access and equity. (May 2022) - Da Silva, Diego; Klumpenhouwer, Willem; Karner, Alex; Robinson, Mitchell; Liu, Rick; Shalaby, Amer
Abstract: While premium transit modes such as commuter rail can improve access to opportunities, the higher fares that accompany these services create barriers to their use. Fare-sensitive access measures require accurate estimation of fare costs between origins and destinations. They are not often included in public transit access analyses because of data limitations and modeling complexity. In this paper, we introduce a flexible and scalable fare calculator that encodes complex fare structures as permissions or "rules" and is able to estimate an origin-destination fare cost from a transit itinerary produced separately. We leverage this fare calculator to examine how access and equity are impacted by fares across seven major urban areas in the United States. We find that fares can act as a substantial barrier to job access, this barrier is not equitably distributed across sociodemographic groups within and between cities, and changes in transit service due to the Covid-19 pandemic has affected access disparities.